Effects of foreign mand training on the emergence of foreign tact and listener responses for Chinese‐speaking children with autism spectrum disorder. (5th January 2023) - Hu, Xiaoyi; Lee, Gabrielle T.; Pan, Qichao; Gilic, Lina; Zeng, Songtian
Abstract: In China, there is an increasing demand for preschool children with autism spectrum disorder (ASD) enrolled in general education to learn English vocabulary. The purpose of this study was to evaluate the effect of foreign mand training in English on the acquisition of mand responses, and the emergence of tact and listener responses for three Chinese‐speaking preschool children (boys; 4–5 years of age) with ASD. Echoic‐to‐mand training was implemented to teach mands in English. The study employed a concurrent multiple‐probe design across behaviors. The results of the study indicated that the training was effective in the acquisition of mand responses. Moreover, untaught tacts and listener responses for the same vocabulary emerged without explicit training. Implications for small‐group mand training in foreign language acquisition were discussed.